Comparison of Cinematic Rendering and Computed Tomography for Speed and Comprehension of Surgical Anatomy - Elshafei, Moustafa; Binder, Johannes; Baecker, Justus; Brunner, Maximilian; Uder, Michael; Grützmann, Robert; Krautz, Christian; Weber, Georg (JAMA Surgery, 2019)
Importance: Three-dimensional (3-D) volume rendering has been shown to improve visualization in general surgery. Cinematic rendering (CR), a novel 3-D visualization technology for postprocessing of computed tomographaphy (CT) images, provides photorealistic images with the potential to improve visualization of anatomic details. Objective: To determine the value of CR for the comprehension of the surgical anatomy. Design, Setting, and Participants: This preclinical, randomized, 2-sequence crossover study was conducted from February to November 1, 2018, at University Hospital of Erlangen, Germany. The 40 patient cases were evaluated by 18 resident and attending surgeons using a prepared set of CT and CR images. The patient cases were randomized to 2 assessment sequences (CR-CT and CT-CR). During each assessment period, participants answered 1 question per case that addressed crucial issues of anatomic understanding, preoperative planning, and intraoperative strategies. After a washout period of 2 weeks, case evaluations were crossed over to the respective second image modality. Main Outcomes and Measures: The primary outcome measure was the correctness of answers. Secondary outcome was the time needed to answer. Results: The mean (SD) interperiod differences for the percentage of correct answers in the CR-CT sequence (8.5% [7.0%]) differed significantly from those in the CT-CR sequence (-13.1% [6.3%]) (P <.001). The mean (SD) interperiod differences for the time spent to answer the questions in the CR-CT sequence (-18.3 [76.9] seconds) also differed significantly from those in the CT-CR sequence (52.4 [88.5] seconds) (P <.001). Subgroup analysis revealed that residents as well as attending physicians benefitted from CR visualization. Analysis of the case assessment questionnaire showed that CR added significant value to the comprehension of the surgical anatomy (overall mean [SD] score, 4.53 [0.75]). No carryover or period effects were observed. Conclusions and Relevance: The visualization with CR allowed a more correct and faster comprehension of the surgical anatomy compared with conventional CT imaging, independent of level of surgeon experience. Therefore, CR may assist general surgeons with preoperative preparation and intraoperative guidance..
CRIS-Team Scopus Importer:2019-06-18

Prognostic subdivision of pT2 rectal carcinomas - Merkel, Susanne; Weber, Klaus; Brunner, Maximilian; Baecker, Justus; Agaimy, Abbas; Göhl, Jonas; Hohenberger, Werner; Schellerer, Vera; Grützmann, Robert (International Journal of Colorectal Disease, 2019)
Purpose The aim of the present study is to explore the prognostic impact of a subdivision of pT2 by the depth of invasion into the muscularis propria in rectal carcinomas.
CRIS-Team WoS Importer:2019-04-18

Risk factors for appendiceal neoplasm and malignancy among patients with acute appendicitis - Brunner, Maximilian; Lapins, Philipp; Langheinrich, Melanie; Baecker, Justus; Krautz, Christian; Kersting, Stephan; Grützmann, Robert; Maak, Matthias; Weber, Georg (International Journal of Colorectal Disease, 2019)
Purpose: Non-operative management of acute uncomplicated appendicitis has shown promising results but might carry the risk of delayed diagnosis of premalignant or malignant appendiceal tumors found by chance in 0.7–2.5% of appendiceal specimen after appendectomy. Purpose of this study was to analyze whether appendiceal tumors are associated with a complicated appendicitis and to determine risk factors for appendiceal neoplasm and malignancy in patients with acute appendicitis. Methods: We performed a retrospective analysis of 1033 adult patients, who underwent appendectomy for acute appendicitis from 2010 to 2016 at the University hospital Erlangen. Data included patients’ demographics; comorbidities; pre-, intra- and postoperative findings; and histopathological results. Complicated appendicitis was defined in the presence of perforation or abscess. Results: Appendiceal neoplasm respectively malignancy rate was 2.8% respectively 1.5%. Using univariate analysis, we identified seven risk factors at least for appendiceal neoplasm or malignancy: age, ASA, C-reactive protein, appendiceal diameter, perforation, intraoperative perithyphilitic abscess, and complicated appendicitis. Risk for appendiceal neoplasm or malignancy was 4.4% respectively 2.7% in complicated acute appendicitis compared to 2.0% respectively 1.0% in uncomplicated appendicitis (p = 0.043 respectively p = 0.060). In multivariate analysis, age ≥ 50 years and a diameter of the appendix in the sonography ≥ 13 mm were independent risk factors predicting the presence of appendiceal neoplasm and malignancy. Conclusion: Among patients with appendicitis, there are relevant risk factors predicting appendiceal tumors, especially age and appendiceal diameter in sonography. But the identified risk factors have a low sensitivity and specificity, so obtaining a confident preoperative diagnosis is challenging.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Appendectomy; Appendiceal neoplasm; Complicated appendicitis; Malignancy; Risk factors

Treatment with the Neurotrophic Protein S100 Calcium-Binding Protein B Increases Synaptogenesis after Traumatic Brain Injury - Baecker, Justus; Wartchow, Krista; Sehm, Tina; Ghoochani, Ali; Buchfelder, Michael; Kleindienst, Andrea (Journal of Neurotrauma, 2019)
Release of neurotrophic and growth factors such as S100 calcium-binding protein B (S100B) yields an endogenous repair mechanism following traumatic brain injury (TBI). Although nanomolar S100B concentrations enhance hippocampal progenitor cell proliferation, neuronal differentiation, and cognitive recovery, micromolar concentrations may foster inflammatory effects counteracting neuroplasticity. The purpose of the present study was to investigate the effect of S100B on synaptogenesis and microglial activation following experimental TBI. Male Sprague-Dawley rats (n = 40) were subjected to lateral fluid percussion or sham injury, and S100B (50 ng/h) or phosphate buffered saline (PBS) was infused into the lateral ventricle for 7 days using osmotic micropumps. The animals were euthanized on day 5 or, 5 weeks post-injury, and 5 mu m sections, 100 mu m apart (bregma -3.3 to -5.6mm) were analyzed histologically. Cell proliferation was assessed injecting the mitotic marker Bromodeoxyuridine (BrdU) on day 2. S100B enhanced significantly the synaptophysin (SYN) expression and microglial activation (ectodysplasin [ED1]) in the hippocampus in TBI and uninjured sham animals. The glial activation (glial fibrillary acidic protein [GFAP], S100B immunoreactive cells), axonal injury (APP) and cell death (terminal deoxynucleotidyl transferase dUTP nick end labeling [TUNEL]) were not altered. Triple-labelling with BrdU, NeuN, and SYN confirmed a significant participation of S100B in hippocampal synaptogenesis in TBI and uninjured sham animals. Our results demonstrate that S100B augments hippocampal neuro- and synaptogenesis in TBI and uninjured sham animals, thereby improving cognitive function as demonstrated earlier. The S100B-induced microglial activation does not counteract this effect within the first 5weeks. Further studies are required to elucidate respective cellular signaling mechanisms and possible long-term effects.
CRIS-Team WoS Importer:2019-11-26